ANALISIS FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN RISIKO KEJADIAN HIPERTENSI PADA USIA DEWASA MUDA DI PUSKEMAS BATANG BERUH KECAMATAN SIDIKALANG KABUPATEN DAIRI TAHUN 2019 - SUSIANI .; SONNY PRIAJAYA; ASIMA SIRAIT (LP2MTBM MAKARIOZ, 2019)
Hypertension or high blood pressure is a problem found in society in both developed and developing countries including Indonesia. Hypertension is a condition of increasing systolic blood pressure more than 140 mmHg and diastolic more than 90 mmHg. The purpose of this study was to analyze the risk factors for the incidence of hypertension in young adults in Batang Beruh Health Center, Sidikalang District, 2019. This type of research is analytic correlation research with case-control design. The population in this study were hypertensive patients at the age of 18-40 years who went to the Batang Beruh Health Center Sidikalang District as many as 42 people as well as residents aged 18-40 years who were not hypertensive patients who went to the Puskesmas as many as 42 people. The data analysis method used in this study consisted of univariate, bivariate and multivariate analysis. The results of the study were obtained: there was a correlation between genetic risk factors (p = 0,000), alcohol consumption (p = 0,040), coffee consumption (p = 0,046), smoking (p = 0,001), salt consumption (p = 0,001), physical activity (p = 0,033), food (p = 0.003) and stress (p = 0.000) with the incidence of hypertension in young adults. Risk factors that are dominantly associated with the incidence of hypertension are genetic risk factors (p = 0,000, Exp (B) = 8,159). It is recommended that hypertension sufferers and the public be able to maintain a healthy lifestyle by carrying out a healthy diet, doing physical activities such as exercise regularly and being able to maintain psychology to avoid stress and the health center can socialize healthy life to avoid health problems such as hypertension.